Strategies for Using Learning Technology to Improve Student Academic Achievement - Nita Sunarya Herawati; FizianYahya (Journal of Practice Learning and Educational Development, 2025)
This research aims to understand the strategies for using learning technology at SMK Darussolihin NW Kalijaga. And what are the obstacles and hindering factors in using technology in the learning process. The method used by the researcher is descriptive qualitative. Data collection techniques thru observation, interviews, and documentation. Data analysis thru data reduction, data presentation, and data verification. The research results show that the strategy of using learning technology to improve student achievement at SMK Darussolihin NW Kaijaga began with planning and work meetings to reach an understanding of the importance of using learning technology to enhance the effectiveness of the learning process up to the assessment process, and then facilitating teachers in the learning process. The obstacles in the implementation of using learning technology are not too significant; there are only a few issues such as some teachers being less prepared and not fully maximizing the use of technology in the learning process.